1999
DOI: 10.1002/1529-0131(199906)42:6<1219::aid-anr19>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Does rheumatoid arthritis remit during pregnancy and relapse postpartum?: Results from a nationwide study in the United Kingdom performed prospectively from late pregnancy

Abstract: Objective. To ascertain the influence of pregnancy on disease activity in women with rheumatoid arthritis (RA) during pregnancy and postpartum.Methods. One hundred forty pregnant women were recruited from a nationwide campaign and were followed prospectively in the last trimester and at 1 and 6 months postpartum. Standardized assessment of joint symptoms, examination of inflamed joints, and the Health Assessment Questionnaire (HAQ) were the main measures of disease activity.Results. There was only a modest fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1
12

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(115 citation statements)
references
References 23 publications
5
90
1
12
Order By: Relevance
“…The median HAQ score of our pregnant patients with RA was 1.0 at the third trimester, and is comparable with the median HAQ score of 0.9 calculated at the third trimester of 140 pregnant patients with inflammatory arthritis prospectively studied by Barrett et al from late pregnancy to postpartum (5). At the third trimester, the patients in the study by Barrett et al completed 2 HAQs, one pertaining to recalled disability before pregnancy and one to current disability.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The median HAQ score of our pregnant patients with RA was 1.0 at the third trimester, and is comparable with the median HAQ score of 0.9 calculated at the third trimester of 140 pregnant patients with inflammatory arthritis prospectively studied by Barrett et al from late pregnancy to postpartum (5). At the third trimester, the patients in the study by Barrett et al completed 2 HAQs, one pertaining to recalled disability before pregnancy and one to current disability.…”
Section: Discussionsupporting
confidence: 82%
“…The retrospective design of their study may have introduced recall bias. Postpartum, however, the median HAQ scores were again comparable: our patients had a median score of 0.75 and their patients a median score of 0.60 (5).…”
Section: Discussionmentioning
confidence: 52%
“…The influence of hormonal changes during pregnancy (estrogen and prolactin) on the immune system is complex and is still not completely understood (20). There is a trend toward clinical improvement in RA patients during pregnancy, but usually there is a worsening of the disease after delivery (21). Glycosylation of IgG, a posttranslational modification, decreases during pregnancy and increases postpartum, both in normal pregnancies and in pregnancies in women with RA (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent prospective study has demonstrated extensive variation in the effect that pregnancy may have on rheumatoid arthritis, with only 16% of study participants experiencing complete remission during pregnancy and >25% suffering considerable disability [2].…”
Section: Introductionmentioning
confidence: 99%